Estimating Amount of Forage in Hay Fields and Pastures - Tim Wilson; Cindy Sanders; Jacque Breman; Lynn Sollenberger (EDIS)
Forage serves as the primary source of nutrients for livestock in Florida, and efficient use of forage is critical to the livelihood of Florida farmers and ranchers. Estimating the amount of forage in a pasture can provide useful information when making management decisions. There must be enough material in the field to justify the cost of using harvesting equipment; otherwise, the area should be grazed. This 2-page fact sheet contains instructions for a simple method to determine the approximate amount of forage in hay fields and pastures. Written by T. Wilson, C. Sanders, J. Breman, and L. Sollenberger, and published by the UF Department of Agronomy, March 2012.